Expanding the genotypic spectrum of Perrault syndrome. Issue 2 (1st April 2016) - Demain, L.A.M.; Urquhart, J.E.; O'Sullivan, J.; Williams, S.G.; Bhaskar, S.S.; Jenkinson, E.M.; Lourenco, C.M.; Heiberg, A.; Pearce, S.H.; Shalev, S.A.; Yue, W.W.; Mackinnon, S.; et al.
Abstract : Abstract : Perrault syndrome is a rare autosomal recessive disorder characterized by sensorineural hearing loss (SNHL) in both sexes and primary ovarian insufficiency in 46, XX karyotype females. Biallelic variants in five genes are reported to be causative: HSD17B4, HARS2, LARS2, CLPP and C10orf2 . Here we present eight families affected by Perrault syndrome. In five families we identified novel or previously reported variants in HSD17B4, LARS2, CLPP and C10orf2 . The proband from each family was whole exome sequenced and variants confirmed by Sanger sequencing. A female was compound heterozygous for a known, p.(Gly16Ser) and novel, p.(Val82Phe) variant in D‐bifunctional protein ( HSD17B4 ). A family was homozygous for mitochondrial leucyl aminocyl tRNA synthetase (mtLeuRS) ( LARS2 ) p.(Thr522Asn), previously associated with Perrault syndrome. A further family was compound heterozygous for mtLeuRS, p.(Thr522Asn) and a novel variant, p.(Met117Ile). Affected individuals with LARS2 variants had low frequency SNHL, a feature previously described in Perrault syndrome. A female with significant neurological disability was compound heterozygous for p.(Arg323Gln) and p.(Asn399Ser) variants in Twinkle ( C10orf2 ). A male was homozygous for a novel variant in CLPP, p.(Cys144Arg). In three families there were no putative pathogenic variants in these genes confirming additional disease‐causing genes remain unidentified. We have expanded the spectrum of disease‐causing variants associated with Perrault syndrome.